2020
DOI: 10.32870/ap.v12n1.1786
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of the attitudes towards ICT of education students according to gender and educational modality

Abstract: Diagnosis of the attitudes towards ICT of education students according to gender and educational modality Diagnóstico de las actitudes hacia las TIC de estudiantes de educación acorde al género y modalidad educativa

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 52 publications
0
14
0
2
Order By: Relevance
“…Importantly, the students must show positive attitude and approach towards the use of ICT tools in order to further the course of education in higher institutions of learning. Despite the fact that numerous studies (Sipilä, 2009;European Commission, 2013;Shaukenova, 2016;García-Martínez et al, 2020;Guillén-Gámez et al, 2020) have shown that most students exhibit favourable attitudes and high expectations (Courtois et al, 2014) regarding the use of ICT tools in education, there are still certain flaws on the part of the learners such as lack of coordination, control and adverse peer influence, that call for attention.…”
Section: The Role Of Studentsmentioning
confidence: 99%
“…Importantly, the students must show positive attitude and approach towards the use of ICT tools in order to further the course of education in higher institutions of learning. Despite the fact that numerous studies (Sipilä, 2009;European Commission, 2013;Shaukenova, 2016;García-Martínez et al, 2020;Guillén-Gámez et al, 2020) have shown that most students exhibit favourable attitudes and high expectations (Courtois et al, 2014) regarding the use of ICT tools in education, there are still certain flaws on the part of the learners such as lack of coordination, control and adverse peer influence, that call for attention.…”
Section: The Role Of Studentsmentioning
confidence: 99%
“…Studies have also compared attitudes towards ICT as a function of sex, although there is little agreement in the results. Some studies [42] found more positive attitudes in men in the cognitive and behavioral components, whereas other studies differ, finding higher, more significant scores from women [23,43]. In any case, it is important to look at this topic more deeply, and especially to consider specific aspects of the Costa Rican setting, where significant efforts are being made to encourage women to do technological and scientific courses, and to increase their employability in these sectors [44].…”
Section: University Students' Attitudes Towards Ictmentioning
confidence: 99%
“…The ACB model has been repeatedly used to study students' and teachers' attitudes towards digital technologies in education [45][46][47][48][49][50]. For example, X.G.…”
Section: Introductionmentioning
confidence: 99%